A Complete course in canning and related processes - Featherstone, Susan (Amsterdam Woodhead Publishing, 2015)
"A Complete Course in Canning and Related Processes, Fourteenth Edition: Fundamental Information on Canning provides readers with a complete course on canning.This latest edition continues the tradition for both professionals in the canning industry and students who have benefitted from this collection for over 100 years. It contains extensively revised and expanded coverage, and the three-title set is designed to cover all phases of the canning process, including planning, processing, storage, and quality control"--Provided by publisher.
v. 1. Fundamental information on canning -- v. 2. Microbiology, packaging, HACCP and ingredients -- v.3. Processing procedures for canned food products.
Includes bibliographical references and index.
Keywords: Canning and preserving